Improving Gross Motor Skills of 5-6-Year-Old Children Through Rhythmic Gymnastics Activities at PAUD Surya Kasih - Karyadi, Agung Cahya; Suri, Noviana (CV. Edutechnium Indonesia, 2024)
The purpose of this study is to describe how to improve gross motor skills, specifically jumping and kicking, through rhythmic gymnastics using used tire props. The study was conducted on children aged 5–6 years at PAUD Suryakasih Griya Tipar Cakung, Jakarta. The research method used in this study is Classroom Action Research (CAR). This study follows the Kemmis and Taggart model, where each cycle follows systematic steps according to research principles and parameter requirements. The research stages include: (1) planning, (2) action, (3) observation, and (4) reflection. Before conducting the study, a pre-action assessment was carried out to determine the initial percentage of children's gross motor skill improvement. The results showed an increase from the initial condition of 25.71%, which improved to 56.84% in cycle 1, and further increased to 71.78% in cycle 2. The implication of this study is that rhythmic gymnastics movements (jumping and kicking) can enhance gross motor skills in Group B children at PAUD Suryakasih.